DEMENTIA - Yulson Rasyid; Reno Sari Chaniago (PT. Anagata Sembagi Education, 2025)
Dementia is a progressive neurodegenerative syndrome characterized by cognitive decline that significantly impairs daily activities and individual independence. This article aims to comprehensively review the clinical aspects of dementia, including epidemiology, classification, risk factors, signs and symptoms, diagnosis, and both pharmacological and non-pharmacological management strategies. The method used is a thematic narrative literature review based on scientific references and current clinical guidelines. Findings indicate that Alzheimer's disease is the most common form of dementia, with major risk factors including advanced age and vascular conditions. Diagnosis is established through neurobehavioral history, physical examination, cognitive tests (MMSE, MoCA, CDT), and neuroimaging. Treatment involves cholinesterase inhibitors (donepezil, rivastigmine), NMDA receptor antagonists (memantine), and non-pharmacological interventions such as cognitive therapies and a person-centered care approach. In conclusion, dementia management requires a multidisciplinary approach involving early detection, symptom control, and comprehensive support to improve patients’ quality of life.